Analysis of Learning Materials for Civic Education in development character in elementary schools - Acesta, Arrova (International Conference on Elementary Education, 2020)
This research is motivated by the low character of the responsibility of students in Ki Hajar Dewantara Elementary School, Kramatmulya District, Kuningan Regency. The purpose of this research is that the character of responsibility can be embedded in students, so through the Civics subject, students learn about the rights and obligations as students, as citizens, and recognize rights and obligations according to their respective roles. So in this case, it is necessary to analyze the implementation of teaching materials rights and obligations as well as the implementation of responsibilities, so that students have a responsible attitude towards the obligations given in studying Civics. This research uses survey research type. The research was conducted at the Ki Hajar Dewantara Elementary School, Kramatmulya District, Kuningan Regency. The data of this study were obtained from the results of filling out the questionnaire on grade V. students of the . The results of the analysis of teaching materials rights and obligations were concluded showing very good relevant categories. The results of research on the implementation of student responsibilities in the Elementary School Ki Hajar Dewantara on Civics subjects show relevance in good categories. It states that through the implementation of teaching materials rights and obligations at the Ki Hajar Dewantara Elementary School can develop the character of responsibility on students